Teori Pengembangan Kreativitas Pendidikan dalam Persfektif Anak Usia Dini - Ulfa, Mutia (Jurnal Aktual Pendidikan Indonesia, 2022)
Education is the process of changing a person's attitudes and behaviors through training, instruction, education, and instruction. Education for a person is very important for a person, from birth to adulthood to death, it is necessary to be educated. A child's development each year determines an adult's quality of life. Children, regardless of age, are characters with their own uniqueness and personality. Growth and physical development play an important role in survival. Growth and physical development affect child development and other dimensions of development. This study uses library research or library research in its approach. It is known that approaches to the study of creativity can be done through various theories. To understand creativity theory, Treffinger and Taylor divided creativity theory into psychoanalytic, humanistic, psychometric, associative, and Divided into 5 groups of cognition.